Ecofriendly Removal of Aluminum and Cadmium Sulfate Pollution by Adsorption on Hexanoyl-Modified Chitosan - Berthold Reis; Konstantin B. L. Borchert; Martha Kafetzi; Martin Müller; Karina Haro Carrasco; Niklas Gerlach; Christine Steinbach; Simona Schwarz; Regine Boldt; Stergios Pispas; Dana Schwarz (Polysaccharides, 2022)
The purity and safety of water as a finite resource is highly important in order to meet current and future human needs. To address this issue, the usage of environmentally friendly and biodegradable adsorbers and flocculants is essential. Chitosan, as a biopolymer, features tremendous properties as an adsorber and flocculant for water treatment. For the application of chitosan as an adsorber under acidic aqueous conditions, such as acid mine drainage, chitosan has been modified with hydrophobic hexanoyl chloride (H-chitosan) to reduce the solubility at a lower pH. In order to investigate the influence of the substitution of the hexanoyl chloride on the adsorption properties of chitosan, two chitosans of different molecular weights and of three different functionalization degrees were analyzed for the adsorption of CdSO4(aq) and Al2(SO4)3(aq). Among biobased adsorbents, H-chitosan derived from the shorter Chitosan exhibited extraordinarily high maximum adsorption capacities of 1.74 mmol/g and 2.06 mmol/g for Cd2+ and sulfate, and 1.76 mmol/g and 2.60 mmol/g for Al3+ and sulfate, respectively.